2D MOF Nanosensor‐Integrated Digital Droplet Microfluidic Flow Cytometry for In Situ Detection of Multiple miRNAs in Single CTC Cells. Issue 32 (14th July 2022) - Chen, Junyue; Oudeng, Gerile; Feng, Hongtao; Liu, Sixi; Li, Hung‐Wing; Ho, Yi‐Ping; Chen, Yan; Tan, Ying; Yang, Mo
Abstract: Current circulating tumor cells (CTCs) detection strategies based on surface epithelial markers suffer from low specificity in distinguishing between CTCs and epithelial cells in hematopoietic cell population. Tumor‐associated miRNAs within CTCs are emerging as new biomarkers due to their high correlation with tumor development and progress. However, in‐situ simultaneous analysis of multiple miRNAs in single CTC cell is still challenging. To overcome this limitation, a digital droplet microfluidic flow cytometry based on biofunctionalized 2D metal‐organic framework nanosensor (Nano‐DMFC) is developed for in situ detection of dual miRNAs simultaneously in single living breast cancer cells. Here, 2D MOF‐based fluorescent resonance energy transfer (FRET) nanosensors are established by conjugating dual‐color fluorescence dye‐labeled DNA probes on MOF nanosheet surface. In the Nano‐DMFC, 2D MOF‐based nanoprobes are precisely microinjected into each single‐cell encapsulated droplets to achieve dual miRNA characterization in single cancer cell. This Nano‐DMFC platform successfully detects dual miRNAs at single‐cell resolution in 10 mixed positive MCF‐7 cells out of 10 000 negative epithelial cells in serum biomimic samples. Moreover, this Nano‐DMFC platform shows good reproductivity in the recovery experiment of spiked blood samples, which demonstrate the high potential for CTC‐based cancer early diagnosis and prognosis. Abstract : A digital droplet microfluidic flow cytometry based on a biofunctionalized 2D metal‐organic framework nanosensor (Nano‐DMFC) is developed for in situ detection of dual miRNAs simultaneously in single living breast cancer cells. This Nano‐DMFC platform shows good reproductivity in the recovery experiment of spiked blood samples, which demonstrated the high potential for circulating tumor cell (CTC)‐based cancer early diagnosis and prognosis.